Measures of functional performance and their association with hip and thigh strength - Kollock, R.; Van Lunen, B. L.; Ringleb, S. I.; Oñate, J. A. (Journal of Athletic Training, 2015)
Context: Insufficient hip and thigh strength may increase an athlete's susceptibility to injury. However, screening for strength deficits using isometric and isokinetic instrumentation may not be practical in all clinical scenarios.